Synthesis and physicochemical characterization of a novel adsorbent based on yttrium silicate: A potential material for removal of lead and cadmium from aqueous media - Litrenta Medeiros, Vinicius [UNESP]; De Araujo, Leandro Goulart; Rubinho Ratero, Davi [UNESP]; Silva Paula, Alex [UNESP]; Ferreira Molina, Eduardo; Jaeger, Christian; Marumo, Júlio Takehiro; Nery, José Geraldo [UNESP] (Elsevier, 2020)
A new metallosilicate based on yttrium was synthesized and characterized by XRD, FT-IR, 29Si MAS-NMR, and 89Y MAS-NMR. The mixed framework of the material was confirmed by the detection of distinct chemical shift groups using 29Si MAS-NMR (at -82 to -87 ppm, -91 to -94 ppm, -96 to -102 ppm, and -105 to -108 ppm), as well as four distinct chemical shifts in the 89Y MAS-NMR spectrum (at -89, -142, -160, and -220 ppm). Adsorption and kinetic analyses indicated the potential of the new material for the removal of lead and cadmium from aqueous media. The adsorption results for lead indicated that dynamic equilibrium was reached after five hours, with total lead removal of around 94 %, while for cadmium it was reached in the first hour, with total cadmium removal of around 74 %. The adsorptions of lead and cadmium were modeled using pseudo-first order (PFO) and pseudo-second order (PSO) kinetic models. Although both models provided high R2 values (0.9903 and 0.9980, respectively), the PSO model presented a much lower χ2red value (4.41 × 10-4), compared to the PFO model (2.12 × 10-3), which indicated that the rate-limiting step was probably due to the chemisorption of lead from the solution onto the yttrium-based metallosilicate.
Keywords: 29Si; 89Y MAS-NMR; Adsorption; Cadmium and lead remediation; Chemisorption; Yttrium silicates